Evidence of development of underutilised crops and their ecosystem services in Europe: a systematic mapping approach - Todd Jenkins; Sofie Landschoot; Kevin Dewitte; Geert Haesaert; John Reade; Nicola Randall (CABI Agriculture and Bioscience)
Abstract Background Growing interest in agrobiodiversity and sustainable agricultural practices has stimulated debates on diversifying cropping systems, furthering the potential for the reintroduction of underutilised crops. These crops may support multiple ecosystem services and enhance food security and agricultural value chains. This study used a systematic mapping approach to collate and summarise the state of research literature addresses the research question: What is the evidence for ecosystem service provision and economic value of underutilised crops? We focused on oats, triticale, hull-less barley, narrow-leaved lupin, buckwheat and faba beans due to their limited use in Europe, their broad gene pool, ecological benefits, and nutritional value. Method Three academic databases were used to identify research articles investigating the impacts of using the six underutilised crops of interest on outcomes including breeding, agronomic traits, nutrition and health, and economic values. In addition, current and recently completed European projects were searched to identify ongoing relevant research. After screening for relevance, data was extracted from all included articles and projects and imported into a spreadsheet for cross-tabulation and to produce descriptive statistics. Results From an initial 34,522 articles identified by the searches, 1346 relevant primary research articles containing 2229 studies were included. A total of 38 relevant European projects were identified, with 112 research results or goals relating to the six underutilised crops. Faba bean was the most common crop in both European projects and published literature. No current projects had a focus on hull-less barley. Agronomic traits were the most common primary research topic across the crops (56.39%), with oats and faba bean being well researched. Hull-less barley was the least studied crop across all topics. Within sub-topics related to specific ecosystem services, desirable traits, disease, weed and pest control all ranked highly, whilst invertebrate diversity and nitrogen fixation ranked lowest. Conclusion Primary research varies between crops and topics, with hull-less barley receiving the least interest. Key knowledge gaps were identified in all crops across all topics relating to breeding tools, breeding for desirable traits, agronomic traits of buckwheat, narrow-leaved lupin and hull-less barley, inclusion of the crops in human nutrition and health, and the socioeconomics of these crops. Evidence presented in this map could inform further research areas with these crops and aid future policy making for the inclusion of these crops in rotations and practices that could benefit all stakeholders along the food systems value chain.